Limited Impact of a WhatsApp‑Based Motivational Messaging Program Grounded in Swanson’s Caring Theory on Nurses’ Compassion Fatigue and Job Satisfaction - R. R. Woro Sulistiyowati; Fitriana Suprapti; Bantari Wisynu Kusuma Wardhani (FORIKES, 2026)
Compassion fatigue is a form of emotional exhaustion experienced by nurses as a result of repeated exposure to patients’ suffering, and this condition can negatively affect job satisfaction. This study aimed to analyze the effect of a motivational message program delivered via WhatsApp on reducing compassion fatigue and its impact on improving nurses’ job satisfaction. A quasi-experimental design with a pretest–posttest and control group was employed. The intervention consisted of motivational messages sent regularly for 21 days to the intervention group. Compassion fatigue and job satisfaction were measured before and after the intervention using questionnaire, and the data were analyzed using parametric statistical tests. The paired samples t-test showed no significant difference between pretest and posttest scores in the intervention group (p = 0.903), suggesting that motivational messages via WhatsApp alone are insufficient to decrease compassion fatigue. Furthermore, the reduction in compassion fatigue did not have a significant impact on improving job satisfaction. Although there was an average increase of 1.39 points, this change was not statistically significant (p = 0.388). Between-group analysis also revealed no significant differences between the intervention and control groups in either compassion fatigue or job satisfaction (p > 0.05). In conclusion, the WhatsApp-based motivational messaging program has not been proven effective in reducing compassion fatigue or improving nurses’ job satisfaction. Future research should develop more comprehensive interventions, such as peer support group programs, that enable nurses to share experiences and provide mutual support.Keywords: compassion fatigue; motivational message; WhatsApp; job satisfaction; nurses